Mapping Practices of Social Control: A Foucauldian Analysis of Urban Space - ŠUPA, MARYJA (Kriminologijos studijos, 2015)
The aim of this article is to reveal how two Foucauldian modalities of power, disciplinarity and biopolitics, are enacted in urban space as practices of social control and negotiation of norms beyond the limits of sovereign juridical power. The article contributes to other spatial studies based on the Foucauldian perspective in two respects: by combining the analysis of both disciplinarity and biopolitics, and by focusing on an urban neighbourhood, rather than a single institution. The characteristics of built structures in a mixed-use neighbourhood in Vilnius were analysed by combining observation and photo-documentation. Qualitative data analysis and thematic mapping of the data was based on coding categories originated from the Foucault’s discussion on the divides and interrelations of power modalities in his lectures at the College de France. The findings show that each structure, regardless of its function, employs both disciplinary and biopolitical techniques of social control at three distinct levels: a) urban planning, prescribed functionality and its correspondence to actual use; b) means of limiting access, containment and transparency; c) circulation of populations and their compliance to the particular spatial setup they find themselves in.